Martian cratering 12. Utilizing primary crater clusters to study crater populations and meteoroid properties. (29th January 2018) - Hartmann, William K.; Daubar, Ingrid J.; Popova, Olga; Joseph, Emily C. S.
Abstract: Images from Mars Global Surveyor and later images from Mars Reconnaissance Orbiter reveal that roughly half of the meteoroids striking Mars (at meter to few decameter crater diameters) fragment in the Martian atmosphere, producing small clusters of primary impact craters. Statistics of these "primary clusters" yield valuable information about important Martian phenomena and properties of interplanetary bodies, including meteoroid behavior in the Martian atmosphere, bulk strengths of bodies striking Mars, and the fraction of Martian "field secondary" craters, a datum that would improve crater count chronometry. Many Martian impactors fragment at altitudes significantly higher than 18 km above the mean surface of Mars, and we find that most bodies striking Mars and Earth have low bulk strengths, consistent with crumbly or highly fractured objects. Applying statistics of primary clusters at various elevations and independent diameter bins, we describe a technique to estimate the percentage of semirandomly scattered "field secondary" craters. Our provisional estimate of this percentage, in the diameter range ~250 m down to ~22 m, is ~40% to ~80% of the total impacts, with the higher percentages at smaller diameters. Our data argue against earlier suggestions of overwhelming dominance by either primaries or secondaries in this diameter range.